2017
DOI: 10.1080/00365513.2017.1393691
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery reduces fasting total fatty acids and increases n-3 polyunsaturated fatty acids in morbidly obese individuals

Abstract: Our findings suggest that a reduced proportion of the proposed anti-atherogenic n-3 PUFAs characterizes morbidly obese individuals, and that this FA profile is reversed by bariatric surgery, but not by lifestyle intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…Contrary to other studies [21,22], we did not find significant differences between the amount of SFAs in serum after bariatric surgery, suggesting that OAGB-induced weight loss does not influence this group. The proportion of MUFAs in patients with obesity was significantly higher than in lean controls and this persisted after OAGB.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to other studies [21,22], we did not find significant differences between the amount of SFAs in serum after bariatric surgery, suggesting that OAGB-induced weight loss does not influence this group. The proportion of MUFAs in patients with obesity was significantly higher than in lean controls and this persisted after OAGB.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported on proportional changes in PUFAs (as opposed to absolute concentrations as reported in the current study) and observed that, although absolute concentrations of these fatty acids decreased, relative proportions were actually increased following metabolic surgery, thus creating a more favourable lipid profile [29,48,51]. In the study by Walle et al, however, subjects were instructed to consume 3 teaspoons of rapeseed oil and 6 tea spoons of mainly rapeseed oil based spreads daily for at least 1e2 years after their weight loss operation and were instructed to consume fish 2e3 times a week.…”
Section: Discussionmentioning
confidence: 48%
“…Recent studies have also demonstrated decreased levels of the nephrotoxic lipid species mentioned above. Fatty acid profiles are improved 1 year following bariatric surgery, with decreased saturated fatty acids and increased levels of anti-atherogenic polyunsaturated fatty acids (70,71). Interestingly, in the immediate months following bariatric surgery, a transient increase in serum fatty acids has been observed, which may represent augmented lipolysis and mobilization of fatty acids from adipose tissue and other organs (72)(73)(74).…”
Section: B Improvement In Metabolic and Lipid Factorsmentioning
confidence: 99%